1978
DOI: 10.1042/cs0540529
|View full text |Cite
|
Sign up to set email alerts
|

Control of Enzymatically Inactive Renin in man under Various Pathological Conditions: Implications for the Interpretation of Renin Measurements in Peripheral and Renal Venous Plasma

Abstract: 1. Human plasma contains two types of renin: one is active in its native form (active renin), the other has renin-like activity after exposure to low pH (inactive renin). Reactions of acid-activated plasma renin and kidney renin with either homo logous or heterologous substrate showed identical K m values.2. Peripheral venous values for active and inactive renin in essential hypertension (n = 22), renovascular hypertension (n = 14), primary aldosteronism (n = 12), adrenal insufficiency (« = 6) and control subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0

Year Published

1979
1979
2001
2001

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 25 publications
5
32
0
Order By: Relevance
“…Whereas most investigators have concluded that there is no conversion of prorenin to renin in the circulation [1,12,14,15], it has been reported that the rat kidney releases a protease that cleaves renin in the circulation [39]. Others have proposed that prorenin might have in vivo activity, for example, through reversible activation or after its uptake by peripheral tissues [ 12,21,40].…”
Section: Activity Of Infused Proreninmentioning
confidence: 99%
See 2 more Smart Citations
“…Whereas most investigators have concluded that there is no conversion of prorenin to renin in the circulation [1,12,14,15], it has been reported that the rat kidney releases a protease that cleaves renin in the circulation [39]. Others have proposed that prorenin might have in vivo activity, for example, through reversible activation or after its uptake by peripheral tissues [ 12,21,40].…”
Section: Activity Of Infused Proreninmentioning
confidence: 99%
“…It was of particular interest to determine whether prorenin was converted to renin in these cells, because the only known sources of plasma renin in humans and rats are the kidneys [ l, 12,14,15]. Most other tissues that have been found to express the renin gene apparently release only prorenin [ 12,14,[20][21][22][23][24][25][26][29][30][31].…”
Section: Post-transcriptional Events In Renin Gene Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pharmacodynamic responses to these agents have been claimed to be directly related to plasma renin activity (Case et al, 1977), which falls with age (Meade et al, 1983 (Hockings et al, 1985). The pharmacokinetics of enalaprilat in these subjects is described in a separate paper (Hockings et al, 1986 Blood pressures and heart rate recordings were made at these times by means of a semi- Derkx et al, (1978). Angiotensin I generated during incubation of buffer and plasma at 37°C was measured by radioimmunoassay.…”
Section: Introductionmentioning
confidence: 99%
“…The measurements of plasma inactive renin reported by many authors are widely scattered (Derkx et al 1976(Derkx et al , 1978Leckie et al 1977;Sealey et al 1977 a,b ;Kappelgaard et al 1978;Millar et al 1980). Where does this inconsistency come from?…”
Section: Discussionmentioning
confidence: 96%